Impact of public funding of education on economic growth in Macedonia - Abdylmenaf Bexheti; Besime Mustafi (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
The main aim of this study is to investigate the relationship between public spending on education after the process of decentralization and economic growth in Macedonia as low income state. This paper do not have intention to make a picture of education system in Macedonia, how it functions or if education is open to all, but has the aim to measure the public spending on education as a determinant that has impact on economic growth even positive or negative. This paper raise the following important question: 'do all measures of public spending on education promote economic growth?' As a lack of data in developing countries like is Macedonia the specification of empirical models to test the causal effect on public spending on education and growth is paradox and this explain why the road through which public education expenditure affects economic growth is not yet well understood. The inter-relationships between government expenditure and education quality should be taken into account when formulating education policy to promote economic growth (Corray, 2000). The channels by which education can promote growth maybe do not lie to quantity of public spending but on quality of the policy that means where youth end after their education. We investigate the link between public spending on education and economic growth in Macedonia using Logarithmic Multiple Regression Model. We came in conclusion that the model is significant. The result shows negative effect on public spending on education and economic growth in the case of Macedonia. The results also raise another statement 'what exactly are the highly educated workers doing together (that is so sensitive to their being highly educated) if it does not involve things changing at the margin?' (Aghion, et.al 2009). It ends with some key conclusions and recommendations that there has to be founded another channels to produce quality education - skilled labor by which will rise the productivity and economic growth.
Keywords: 330; public expenditures; education; economic growth; real GDP; public investment; skilled labor